The Association between α(4)-Integrin, P-Selectin, and E-Selectin in an Allergic Model of Inflammation - Kanwar, Samina (The Rockefeller University Press, 1997)
In this study, we examined the relationship between the endothelial selectins (P-selectin and E-selectin) and whether they are critical for α(4)-integrin–dependent leukocyte recruitment in inflamed (late phase response), cremasteric postcapillary venules. Animals were systemically sensitized and 2 wk later challenged intrascrotally with chicken ovalbumin. Leukocyte rolling flux, adhesion, and emigration were assessed at baseline and 4 and 8 h postantigen challenge. There was a significant increase in leukocyte rolling flux, adhesion, and emigration in sensitized and challenged mice at both 4 and 8 h. At 8 h, the increase in leukocyte rolling flux was ∼50% inhibitable by an anti–α(4)-integrin antibody, 98% inhibitable by fucoidin (a selectin-binding carbohydrate), and 100% inhibitable by an anti–P-selectin antibody. P-selectin–deficient animals displayed no leukocyte rolling or adhesion at 8 h after challenge. However, at 8 h there were many emigrated leukocytes in the perivascular space suggesting P-selectin–independent rolling at an earlier time point. Indeed, at 4 h postantigen challenge in P-selectin–deficient mice, there was increased leukocyte rolling, adhesion, and emigration. The rolling in the P-selectin– deficient mice at 4 h was largely α(4)-integrin dependent. However, there was an essential E-selectin– dependent component inasmuch as an anti–E-selectin antibody completely reversed the rolling, and in E-selectin and P-selectin double deficient mice rolling, adhesion and emigration were completely absent. These results illustrate that P-selectin underlies all of the antigen-induced rolling with a brief transient contribution from E-selectin in the P-selectin–deficient animals. Finally, the antigen-induced α(4)-integrin–mediated leukocyte recruitment is entirely dependent upon endothelial selectins.